DEVELOPMENT OF A SOLAR BOX FOR COOKING AND WATER HEATING (FULafia Journal of Science and Technology, 2023)
Solar cooking is the utilisation of direct insolation harnessed from the sun as energy source in cooking and water heating. In this study, a device for solar collection and direct utilisation for cooking and water heating was developed. The device consisted of two boxes a smaller box 600 mm × 600 mm × 460 mm insulated with coconut coir of thermal conductivity 0.295Wm-1) -1 placed within a larger box 700 mm × 700 mm ×500 mm. The direct solar insolation (Is), stagnation temperature of the device (Ts), ambient temperature (Ta) andthe wind velocity (V) were measured in accordance with ASHRAE standards. The regression procedure of Mini Tab (v.16) was used to relate the cooker temperature (Tc) with Is, Ts, Ta, and V. The presence of the heat storage unit made it possible to cook beyond 15:00 hours up until 18:00 hours local time while the hot water from the dispensing unit attained temperature of about 650c for most days of testing at about 13:00 ± 0:40 hours and gradually dropped to about 50℃ ± 5℃ by 19:00 hours local time
Keywords: Solar Cooking; Coconut coir; Insolation; Hot water; Rock peddles